(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the problems of translating German and English proverbs and their structural and semantic aspects, and explains them with examples. This process is quite difficult to assess. In particular, proverbs are a genre of Uzbek children’s folklore that has a history of several centuries and is widespread and still actively practiced today.